2022
DOI: 10.3390/ijms23084449
|View full text |Cite
|
Sign up to set email alerts
|

The Ameliorative Effect of Dexamethasone on the Development of Autoimmune Lung Injury and Mediastinal Fat-Associated Lymphoid Clusters in an Autoimmune Disease Mouse Model

Abstract: In our previous study, we revealed the ameliorative therapeutic effect of dexamethasone (Dex) for Lupus nephritis lesions in the MRL/MpJ-Fas lpr/lpr (Lpr) mouse model. The female Lpr mice developed a greater number of mediastinal fat-associated lymphoid clusters (MFALCs) and inflammatory lung lesions compared to the male mice. However, the effect of Dex, an immunosuppressive drug, on both lung lesions and the development of MFALCs in Lpr mice has not been identified yet. Therefore, in this study, we compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Many autoimmune diseases exhibit inflammatory lung lesions and fibrosis, referred to as autoimmune lung disease. Eleva et al [ 9 ] studied the effect of anti-inflammatory corticosteroid dexamethasone on lung injury in the autoimmune mouse model. Their study showed that dexamethasone ameliorates the severity of lung injury, partially through the polarization of macrophages toward the alternatively activated (anti-inflammatory) M2 macrophages.…”
mentioning
confidence: 99%
“…Many autoimmune diseases exhibit inflammatory lung lesions and fibrosis, referred to as autoimmune lung disease. Eleva et al [ 9 ] studied the effect of anti-inflammatory corticosteroid dexamethasone on lung injury in the autoimmune mouse model. Their study showed that dexamethasone ameliorates the severity of lung injury, partially through the polarization of macrophages toward the alternatively activated (anti-inflammatory) M2 macrophages.…”
mentioning
confidence: 99%